Comparing the test–retest reliability of resting‐state functional magnetic resonance imaging metrics across single band and multiband acquisitions in the context of healthy aging. Issue 5 (22nd December 2022) - Cahart, Marie‐Stephanie; O'Daly, Owen; Giampietro, Vincent; Timmers, Maarten; Streffer, Johannes; Einstein, Steven; Zelaya, Fernando; Dell'Acqua, Flavio; Williams, Steven C. R.
Abstract: The identification of meaningful functional magnetic resonance imaging (fMRI) biomarkers requires measures that reliably capture brain performance across different subjects and over multiple scanning sessions. Recent developments in fMRI acquisition, such as the introduction of multiband (MB) protocols and in‐plane acceleration, allow for increased scanning speed and improved temporal resolution. However, they may also lead to reduced temporal signal to noise ratio and increased signal leakage between simultaneously excited slices. These methods have been adopted in several scanning modalities including diffusion weighted imaging and fMRI. To our knowledge, no study has formally compared the reliability of the same resting‐state fMRI (rs‐fMRI) metrics (amplitude of low‐frequency fluctuations; seed‐to‐voxel and region of interest [ROI]‐to‐ROI connectivity) across conventional single‐band fMRI and different MB acquisitions, with and without in‐plane acceleration, across three sessions. In this study, 24 healthy older adults were scanned over three visits, on weeks 0, 1, and 4, and, on each occasion, underwent a conventional single band rs‐fMRI scan and three different rs‐fMRI scans with MB factors 4 and 6, with and without in‐plane acceleration. Across all three rs‐fMRI metrics, the reliability scores were highest with MB factor 4 with no in‐plane acceleration for cortical areas and with conventional single band for subcortical areas. Recommendations for future research studies are discussed. Abstract : We compared the test–retest reliability of three resting‐state fMRI metrics across four different resting‐state modalities and over three visits. Multiband factor 4 with no in‐plane acceleration significantly improved intraclass correlation coefficient (ICC) scores for cortical areas, while single band yielded the best ICC values for subcortical regions. We recommend multiband factor 4 with no in‐plane acceleration for whole brain analyses or analyses focussing specifically cortical regions, and single band for studies with an emphasis on subcortical areas.